Innovative Device for Indocianyne Green Navigational Surgery - Cătălin Aliuș; Nicolae Bacalbașa; Cristian Bălălău (Journal of Mind and Medical Sciences)
Dynamic reality has been integrated into developing surgical techniques, with the goals of providing increased intraoperative accuracy, easier detection of critical anatomical landmarks, and better general results for the patient. Enhancement of the reality in surgical theaters using single or multi sensorial augmenters (haptic, thermic and visual) has been reported with various degrees of success. This paper presents a novel device for navigational surgery and ancillary clinical applications based on the fluorescent properties of Indocyanine Green (ICG), a safe, FDA-approved dye that emits fluorescence at higher wavelengths than endogenous proteins. The latest technological developments and the aforementioned convenient quantum behavior of ICG allow for its effective identification in tissues by means of a complementary metal-oxide semiconductor (CMOS) infrared camera. Following fundamental research on the fluorophor in different biological suspensions and at various concentrations, our team has built a device that casts a beam of excitation light at 780nm and collects emission light at 810-830nm, filtering ambient light and endogenous autofluorescence. The emission light is fluorescent and infrared, unlike visible light. It can penetrate tissues up to 1.6cm in depth, providing after digitization into conventional imaging anatomical and functional data of immense intra-operative value.